Financial Literacy and Financial Technology Education for Adolescents at Santika High School, Cipayung District, Becoming Smart Adolescents in Managing Finances - Maya Sova; Nuraini, Ani; Jaya, Titus Indra; Rosmiati, Eros; Rushadiyati, Rushadiyati; Harfika, Meiana (PT FORMOSA CENDEKIA GLOBAL, 2023)
Literacy is an important factor in understanding and increasing knowledge, including regarding finance, while financial technology is a form of technology-based service which, if financial literacy and financial technology are combined, not only those of productive age who have income but also all age groups can become smarter and more confident. in making financial decisions to improve the quality of life in the future. In the Bambu apus sub-district area there are several high schools (SMA) where, after a preliminary study, there was a lack of understanding regarding financial management and financial technology. For this reason, it is necessary to provide education to increase teenagers' knowledge about financial literacy and financial technology. The method used in carrying out community service activities is directly at Santika High School in the Bambu Apus sub-district with the theme of increasing financial literacy and financial technology among young upper secondary school students. The implementation of community service activities was carried out by a service team from Respati Indonesia University by explaining material about financial management based on financial technology and material on the types of investments that can be made by teenagers. After carrying out this activity, there was an increase in knowledge and understanding among the participants as seen from the enthusiasm of the participants and the many questions regarding financial literacy and financial technology and their benefits in improving the Indonesian economy.